THE STRATEGIC DIRECTIONS OF LEGAL POLICIES FOR ENSURING INTERNATIONAL SECURITY AND PROTECTING PEACE AND HUMANITY FROM THREATS IN THE CONTEXT OF GLOBALIZATION - Avdeevich Avdeev, Vadim; Anatolievna Avdeeva, Olga; Vasilevna Shagieva, Rosalina; Afanasevich Mashkin, Nikolay; Evgenievna Borisova, Natalia; Borisovich Shirshikov, Vladislav (Revista Inclusiones, 2020)
The article deals with the legal framework for ensuring international security in the context of protecting peace and humanity in the conditions of the intensification of international life and the negative consequences of globalization processes. The initiation of codification by the international community of international means of human protection is due to the growing trend of the threat of war. In the context of the globalization of international life, new conditions for ensuring international security were predetermined by the growing number of subjects in international relations and the presence of mass destruction weapons in countries. As a result, the problem of creating restrictive mechanisms to ensure effective counteraction to foreign aggression was brought to the forefront. New threats and risks to the peace and security of mankind are caused by a sharp decline in the level of the population’s welfare in different countries, the quality of life among the population, the growing pace of internal crisis in states, aggravation of the demographic situation and the development of migration flows. Among the negative phenomena as consequences of the globalization of international life is the search for new sources of resources